Linguistic Landscape and Social Media Discourse of Russian-Speaking Schools in Visaginas (Lithuania) - Šliachtenko, Jevfrosinija (Slavistica Vilnensis, 2025)
Modern sociolinguistics pays great attention to the study of the functioning of languages in a multilingual space. Visaginas is a multilingual town, which is denoted by a range of distinctive features: it is a town with a predominantly Russian-speaking population, in which socio-political changes are taking place. This attracts attention to the current linguistic situation of the town and the language policy realised in it.The article is devoted to the analysis of the Linguistic Landscape and Social Media Discourse of Russian-speaking Schools in Visaginas. The paper also includes a review of the relevant sociolinguistic literature. The analytical part presents the physical and virtual linguistic landscape of Russian-speaking schools in Visaginas. The study of the physical linguistic landscape and virtual linguistic landscape in schools of Visaginas allows us to find out which languages are functioning in this environment, and to determine their status. For the analysis, the linguistic landscape analysis method, the statistical method, and the comparative method were used. The conducted analysis of 6460 units of physical and virtual spaces has revealed the predominance of texts in the Lithuanian language and the practice of its active use not only in the school space, but also in the virtual space of Russian-speaking schools in Visaginas.
Keywords: Visaginas; Russian-speaking schools; linguistic landscape; virtual linguistic landscape; media discourse